Hygienic Requirements for Food and Its Impact on Human Health - Djurabayeva Dilafruz Ergashbaevna (Web of Journals Publishing, 2023)
This article provides a summary of the effects of food hygiene on human health.
Keywords: nutrition, physical work, development, principle, rational, organism, physiological, pathological.